2020
DOI: 10.3390/pharmaceutics12080698
|View full text |Cite|
|
Sign up to set email alerts
|

Antioxidant and Antibacterial Properties of Carbosilane Dendrimers Functionalized with Polyphenolic Moieties

Abstract: A new family of polyphenolic carbosilane dendrimers functionalized with ferulic, caffeic, and gallic acids has been obtained through a straightforward amidation reaction. Their antioxidant activity has been studied by different techniques such as DPPH (2,2′-diphenyl-1-picrylhydrazyl) radical scavenging assay, FRAP assay (ferric reducing antioxidant power), and cyclic voltammetry. The antioxidant analysis showed that polyphenolic dendrimers exhibited higher activities than free polyphenols in all cases. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Amidation reaction was performed using EDCl/HOBt under ultrasound irradiation with 65–78 % yield [32] . Amides have also been synthesized in high yields (81–93 %) with EDCl/HOBt using different solvents like dichloromethane, acetone and tetrahydrofuran under reflux [33,34] . Keeping in view of this versatile uses, we carried out the coupling reaction of 2‐hydrazino‐1,3‐benzothiazole with different aromatic carboxylic acids using EDCl/HOBt in N,N‐dimethyl formamide (DMF) at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Amidation reaction was performed using EDCl/HOBt under ultrasound irradiation with 65–78 % yield [32] . Amides have also been synthesized in high yields (81–93 %) with EDCl/HOBt using different solvents like dichloromethane, acetone and tetrahydrofuran under reflux [33,34] . Keeping in view of this versatile uses, we carried out the coupling reaction of 2‐hydrazino‐1,3‐benzothiazole with different aromatic carboxylic acids using EDCl/HOBt in N,N‐dimethyl formamide (DMF) at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, dendrimers have several positive characteristics for the cosmetics industry ( Figure 7 ) [ 90 ] such as facilitating drug skin permeability and are used in skin and hair care products [ 115 ]. A recent study by Sanz del Olmo et al [ 134 ] reported the synthesis of carbosilane dendrimers functionalized with phenolic acids (ferulic, caffeic, and gallic acids), revealing an improvement in the antioxidant activity and antibacterial capacity of polyphenolic compounds. Therefore, the application of dendritic systems as anchorage platforms for polyphenolic compounds in the cosmetics field would be advantageous [ 134 ].…”
Section: Nanocarriersmentioning
confidence: 99%
“…Del Olmo et al [ 77 ] performed the reaction of amidation-obtained first-generation carbosilane dendrimers functionalized with ferulic acid. These new polyphenolic compounds exhibited higher antioxidant properties than free ferulic acid.…”
Section: Novel Strategies For Ferulic Acid Drug Deliverymentioning
confidence: 99%